Methods for assessing the effectiveness of investment projects in inflationary conditions - Shirinov, B.; Mehraliyev, N.; Mammadli, F.; Ширінов, Б. Г.; Мехралієв, Н. Х.; Маммадлі, Ф. Н. (Харківський національний автомобільно-дорожній університет, 2026)
The evaluation of investment projects under conditions of inflation remains a critical challenge for both researchers and practitioners, particularly in long-term, capitalintensive, or innovative projects. Traditional approaches, which often assume homogeneous inflation and apply a single discount rate, fail to capture the asymmetric and component-specific effects of inflation on project cash flows, potentially leading to biased assessments of profitability and risk. This study proposes a comprehensive methodology for investment project evaluation under heterogeneous inflation, integrating three key innovations: component-specific adjustment of cash flows using inflation deflators, dynamic determination of period-specific discount rates based on the Fisher equation, and the application of scenario and stochastic analyses to quantify uncertainty and risk. The framework enables disaggregation of revenues, operating costs, capital expenditures, taxes, and working capital flows, allowing for precise modeling of inflation effects on each component. Sensitivity analysis and Monte Carlo simulation are employed to evaluate the impact of alternative inflation scenarios, providing a probabilistic distribution of net presentvalue (NPV) and other performance indicators. An illustrative investment project demonstrates that accounting for heterogeneous inflation substantially modifies project valuation compared to classical discounted cash flow (DCF) approaches, revealing structural effects masked under homogeneous assumptions. The proposed methodology enhances the accuracy and objectivity of project appraisal, improves risk-awareness, and supports strategic decision-making under inflationary uncertainty. This study contributes to investment evaluation theory by offering a robust, practical framework that accommodates asymmetric, time-varying inflation dynamics a ndinforms more effective capital allocation in contemporary economic conditions.
Методи оцінювання ефективності інвестиційних проєктів в умовах інфляції
Keywords: inflation; investment projects; accounts receivable; accounts payable; working capital; price indices; discount rate; current expenses; income; forecast; інфляція; інвестиційні проєкти; дебіторська заборгованість; кредиторська заборгованість; обігові кошти; цінові індекси; ставка дисконтування; поточні витрати; доходи; прогноз; 336.76; 10.30977/ЕТК.2225-2304.2026.47.118